PROPERTIES OF SOME NEW CLOSED SETS IN TOPOLOGICAL SPACES - D. MALARVIZHI; C. RAJAN (Utilitas Mathematica, 2025)
In this article, we introduce a new class of generalized closed sets called g^-closed sets in topological spaces. We investigate the relationships among the related to generalized closed sets.